The Effect of The Implementation of The Independent Curriculum on The Motivation and Learning Outcomes Of Pancasila Education In High School Students In Bantaeng Regency - Ilmi, Nur; Suardi, Suardi; Azis, Abdul (Universitas of Muhammadiyah Makassar, 2024)
Improving the motivation and learning outcomes of Pancasila Education is a significant problem in research that is very important to improve. This study aims to determine how implementing the independent curriculum affects the motivation and learning outcomes of Pancasila Education in high school students in Bantaeng Regency. Mixed research methods will be used in this study. The mixed method is a research method that combines elements of quantitative and qualitative approaches in a single study. The Mixed Method research method is an approach that integrates quantitative and qualitative research simultaneously in one study to produce more comprehensive, valid, reliable, and objective data. Top of FormBottom of Form The qualitative data collection techniques of the research include observation, interviews, and documentation. Meanwhile, the quantitative data collection technique uses a Google form questionnaire sent to teachers and students. This research is carried out through several stages, namely preparation, implementation, completion, and preparation of reports. The result of this study is that implementing the independent curriculum effectively affects the motivation and learning outcomes of Pancasila Education in high school students in Bantaeng Regency. The independent curriculum is designed to prioritize the development of students' character and skills. The involvement and activeness of students in learning, as well as the curriculum approach used, emphasizes contextual learning and free and independent learning, which will affect the increase in motivation and impact the learning outcomes of Pancasila Education.